A method for preparing high temperature resistant ceramic fiber felt
By dispersing SiC nanowires and microfibers and preparing ceramic fiber felts coated with silicon sol protectant, a dense glass coating is formed, which solves the problem of oxidation and cracking of ceramic fiber felts in high temperature environments, and achieves long-term high-temperature and anti-oxidation applications above 1500°C.
Patent Information
- Application Number
- CN202510012929.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-06
AI Technical Summary
In high-temperature environments, existing ceramic fiber felts are prone to surface crystallization, uneven thermal stress distribution, and reaction with oxygen, resulting in surface cracking due to surface crystallization, high-temperature and anti-oxidation application capabilities in ultra-high temperature environments are insufficient.
SiC nanowires and SiC microfibers are dispersed by anionic and cationic surfactants to form SiC multi-scale nano/micro ceramic fiber felt matrix, and a silicon sol protectant-coated ceramic fiber felt precursor was prepared by suction filtration, which was heat treated to form a dense and uniform glass coating to prevent oxidation and cracking.
It has achieved long-term high-temperature and anti-oxidation application of ceramic fiber felt above 1500℃, maintained a compression rebound performance of 20~50%, and reduced production costs and preparation cycles.
Smart Images

Figure CN119411308B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high temperature resistant elastic materials, and in particular to a method for preparing high temperature resistant ceramic fiber felt. Background Art
[0002] Ceramic fiber felt is a quilt-type thermal protection material with the characteristics of light weight, low thermal conductivity, good compression resilience, and excellent thermal shock resistance. It is widely used in high-temperature metallurgy, automobile manufacturing, aerospace, building insulation and other fields. It can be divided into oxide fiber felt (SiO2, Al2O3, mullite, etc.) and non-oxide (C, SiC, Si3N4, etc.) according to its chemical composition. When the working temperature of oxide ceramic fiber exceeds 1200℃, surface crystallization will occur. Long-term use will cause uneven distribution of fiber thermal stress due to grain growth and eventually break and fail; non-oxide fiber will react with oxygen in a high-temperature aerobic environment, causing cracking on the fiber surface, so the general working temperature does not exceed 1300℃. In recent years, with the continuous development of industrial technology in related fields, the complex working conditions faced by some high-temperature equipment during operation have put forward higher requirements for the long-term thermal protection performance of ceramic fiber felt in ultra-high temperature extreme environments. The long-term use temperature may exceed the limit working temperature of the existing fiber felt, resulting in the failure of the fiber felt due to structural damage.
[0003] Therefore, it is a major technical challenge in this field to prepare a ceramic fiber felt with stable structure in ultra-high temperature environment through micro-scale structural design. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a high temperature resistant ceramic fiber felt, so as to solve the problems existing in the above-mentioned prior art and realize the long-term high temperature resistant and anti-oxidation application of the ceramic fiber felt above 1500°C.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is to provide a method for preparing a high temperature resistant ceramic fiber felt, the steps comprising:
[0007] dispersing SiC nanowires by using anionic surfactant to obtain SiC nanowire dispersion;
[0008] The SiC micron fiber is dispersed by using a cationic surfactant to obtain a SiC micron fiber dispersion;
[0009] The SiC nanowire dispersion and the SiC micron fiber dispersion are mixed and then subjected to filter pressing treatment, and the mixing-filter pressing treatment is repeated at least once to obtain a SiC multi-scale nano / micro ceramic fiber felt matrix;
[0010] Passing the silica sol protective agent through the SiC multi-scale nano / micro ceramic fiber felt matrix by suction filtration, and obtaining a high temperature resistant ceramic fiber felt precursor (SiC multi-scale ceramic fiber felt coated with silica sol protective agent) after washing and drying;
[0011] The high temperature resistant ceramic fiber felt precursor is heat treated and then cooled to obtain the high temperature resistant ceramic fiber felt.
[0012] The present invention increases the specific surface area of the material by wrapping SiC nanowires on the surface of SiC micron fibers and filling the fiber pores, so that the molten glass phase formed by amorphous SiO2 at high temperature cannot flow radially along the SiC micron fibers, and a dense and uniform glass coating is formed on the surface of the SiC micron fibers, which effectively prevents the oxidation cracking of the SiC fibers when they come into contact with oxygen at high temperatures, thereby improving the high temperature resistance of the material.
[0013] The present invention adopts the method of suction filtration to prepare the high-temperature resistant ceramic fiber felt precursor because only by suction filtration can it be ensured that the silica sol protective agent is distributed on the surface of the SiC multi-scale nano / micro ceramic fiber felt matrix in the form of a coating layer, rather than being distributed only at the overlap position of the SiC nanowires and the SiC micro fibers or agglomerated in the pores of the SiC micro fibers.
[0014] Anionic and cationic surfactants disperse SiC nanowires and SiC microfibers respectively, so that SiC nanowires tend to be wrapped on the surface of SiC microfibers. In this way, the high-temperature resistant ceramic fiber felt finally prepared can be in a high-temperature working environment (1400°C and above). SiC nanowires can prevent the silica sol protective agent from flowing along the SiC microfibers at high temperature, making the coating of the glass phase more uniform.
[0015] When the high temperature resistant ceramic fiber felt precursor is heat treated, the silicon soluble protective agent melts at high temperature, and after cooling, it is transformed into a glass phase, and is evenly wrapped on the surface of the SiC micron fiber to form a protective layer.
[0016] Furthermore, the step of dispersing SiC nanowires using anionic surfactants is:
[0017] After dissolving the stabilizer and the anionic surfactant in water, the SiC nanowires are added and ultrasonically dispersed to obtain a SiC nanowire dispersion.
[0018] Preferably, the mass ratio of the stabilizer, the anionic surfactant and water is 1-3:1-5:1000-2000.
[0019] Preferably, the mass ratio of the sum of the mass of the stabilizer, the anionic surfactant and water to the mass of the SiC nanowires is 400-800:1.
[0020] Preferably, the ultrasonic dispersion time is 10 to 30 minutes.
[0021] Preferably, the anionic surfactant is at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, calcium stearate, sodium fatty alcohol sulfate and sodium ethoxylated fatty acid methyl ester sulfonate.
[0022] Preferably, the stabilizer includes at least one of polyethylene glycol, polyvinyl alcohol, carboxymethyl cellulose, hydroxymethyl cellulose and sodium alginate.
[0023] Furthermore, the step of dispersing SiC micron fibers using a cationic surfactant is:
[0024] After dissolving a stabilizer, a cationic surfactant and an organic polar solvent in water, SiC micron fibers are added and dispersed by ultrasonic to obtain a SiC micron fiber dispersion.
[0025] Preferably, the SiC micron fibers are chopped SiC micron fibers.
[0026] Preferably, the cationic surfactant is at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium bromide chloride, cetylpyridinium chloride, benzalkonium chloride and benzalkonium bromide.
[0027] Preferably, the stabilizer includes at least one of polyethylene glycol, polyvinyl alcohol, carboxymethyl cellulose, hydroxymethyl cellulose and sodium alginate.
[0028] Preferably, the organic polar solvent includes one of ethanol, propylene glycol, N,N-dimethylformamide (DMF), dimethylacetamide (DMAc) and N-methylpyrrolidone (NMP).
[0029] Preferably, the mass ratio of the stabilizer, the cationic surfactant, the organic polar solvent and water is 1-3:1-5:100-200:1000-2000.
[0030] Preferably, the mass ratio of the sum of the mass of the stabilizer, the cationic surfactant, the organic polar solvent and water to the mass of the SiC micron fiber is 500-1000:1.
[0031] Preferably, the ultrasonic dispersion time is 10 to 30 minutes.
[0032] Furthermore, the mass ratio of SiC micron fibers to SiC nanowires in the SiC multi-scale nano / micron ceramic fiber felt matrix is 1-7:1-10.
[0033] Furthermore, the pressure of the filter press is 0.6~0.8MPa.
[0034] Furthermore, the preparation steps of the silica sol protective agent are:
[0035] The organosilicon source, ethanol and water are mixed in a molar ratio of 1:8-15:4-10, stirred at a speed of 300-500 rpm for 10-30 minutes, and then hydrochloric acid is added dropwise. After the addition is completed, the mixture is stirred for 12-20 hours under a closed condition to obtain an organosilicon sol;
[0036] The organic silica sol is then dispersed in ethanol to obtain a silica sol protective agent.
[0037] Preferably, the organic silicon source includes at least one of tetraethyl orthosilicate (TEOS), methyltriethoxysilane (MTES), methyltrimethoxysilane, dimethyldiethoxysilane, dimethyldimethoxysilane, trimethylethoxysilane (TMES), trimethylmethoxysilane, vinyltriethoxysilane and γ-aminopropyltriethoxysilane.
[0038] Preferably, the molar ratio of hydrochloric acid to the organosilicon source is 10 -4 ~10 -3 :1.
[0039] The purpose of adding hydrochloric acid is to promote the hydrolysis reaction.
[0040] Preferably, the mass fraction of the organic silicon source in the silica sol protective agent is 1-3%.
[0041] Furthermore, the vacuum degree of the filtration is -0.1~0.08MPa.
[0042] Furthermore, the volume / mass ratio of the silica sol protective agent to the SiC multi-scale nano / micro ceramic fiber felt matrix is 80-120 mL:2-3 g, preferably 100 mL:2.5 g.
[0043] Furthermore, the drying temperature is 120-150° C. and the drying time is 12-24 hours.
[0044] Furthermore, the heat treatment temperature is 1200-1400° C., and the time is 1-3 hours.
[0045] The second technical solution of the present invention is to provide a high temperature resistant ceramic fiber felt produced by the above preparation method.
[0046] The third technical solution of the present invention is to provide an application of the above-mentioned high-temperature resistant ceramic fiber felt in high-temperature equipment related to the high-temperature industrial field, automobile manufacturing field, aerospace field, and metallurgical industry field.
[0047] The present invention discloses the following technical effects:
[0048] The present invention increases the specific surface area of the high-temperature resistant ceramic fiber felt by wrapping SiC nanowires on the surface of SiC micron fibers, and at the same time prevents the molten glass phase formed on the high-temperature resistant ceramic fiber felt in a high-temperature working environment (1400°C and above) from flowing radially along the SiC micron fibers (the SiC nanowires can play a barrier role), and forms a dense and uniform glass coating on the surface of the micron fibers, effectively preventing the oxidation cracking of the SiC fibers when in contact with oxygen at high temperatures, thereby improving the high-temperature resistance of the material.
[0049] The present invention prepares a layered fiber felt with controllable density and thickness through a process of multiple filter pressing and molding, and still maintains 20-50% compression rebound performance after being subjected to a high temperature environment of 1500°C for a long time.
[0050] The ceramic fiber felt prepared by the present invention is formed by normal pressure drying, which greatly reduces the preparation cycle and production cost of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0052] Figure 1 The SEM images of the SiC multi-scale nano / micro ceramic fiber felt matrix in Example 1 at different magnifications, wherein (a) is 30 times and (b) is 4000 times;
[0053] Figure 2 This is a physical picture of the high temperature resistant ceramic fiber felt prepared in Example 1;
[0054] Figure 3 The SEM images of the high temperature resistant ceramic fiber felt precursor and the high temperature resistant ceramic fiber felt, wherein (a) is the high temperature resistant ceramic fiber felt precursor, (b) is the high temperature resistant ceramic fiber felt magnified 200 times, and (c) is the high temperature resistant ceramic fiber felt magnified 1000 times;
[0055] Figure 4 The SEM images of the high temperature resistant ceramic fiber felt prepared in Example 1 before and after high temperature treatment, wherein (a) is before high temperature treatment, (b) is after heat treatment at 1500°C for 20h, (c) is after heat treatment at 1500°C for 40h, and (d) is after heat treatment at 1500°C for 60h;
[0056] Figure 5The compression rebound properties of the high temperature resistant ceramic fiber felt in Example 1 after being treated at 1500°C for different time periods, wherein (a) is 0h, (b) is 20h, (c) is 40h, (d) is 60h, (e) is 80h, and (f) is 100h;
[0057] Figure 6 The high temperature resistant ceramic fiber felt in Example 1 is compressed to 50% after being subjected to cyclic heat treatment at 1500° C. for 100 hours;
[0058] Figure 7 The SEM images of the high temperature resistant ceramic fiber felt in Example 2 at different magnifications after being treated at 1500°C for 60 hours, wherein (a) is 100 times, (b) is 500 times, and (c) is 1000 times;
[0059] Figure 8 The SEM images of the high temperature resistant ceramic fiber felt in Example 3 after being treated at 1500°C for 60 hours at different magnifications, wherein (a) is 37 times, (b) is 300 times, and (c) is 1000 times;
[0060] Fig. 9 The SEM images of the high temperature resistant ceramic fiber felt in Example 4 at different magnifications after being treated at 1500°C for 60 hours, wherein (a) is 100 times, (b) is 1000 times, and (c) is 850 times;
[0061] Fig.10 The SEM images of the high temperature resistant ceramic fiber felt in Example 5 at different magnifications after being treated at 1500°C for 60 hours, wherein (a) is 35 times, (b) is 1000 times, and (c) is 1000 times;
[0062] Fig.11 The SEM images of the high temperature resistant ceramic fiber felt in Example 6 at different magnifications after being treated at 1500°C for 60 hours, wherein (a) is 35 times, (b) is 950 times, and (c) is 1000 times;
[0063] Fig.12 The SEM images of the high temperature resistant ceramic fiber felt precursors in Examples 7 and 8, wherein (a) to (b) are from Example 7, and (c) to (d) are from Example 8;
[0064] Fig.13 The SEM images of the high temperature resistant ceramic fiber felt precursors in Examples 9 and 10, wherein (a) is Example 9 and (b) is Example 10;
[0065] Fig.14The SEM images of the ceramic fiber felt precursor and the ceramic fiber felt before and after high temperature treatment prepared in Comparative Example 1, wherein (a) is the ceramic fiber felt precursor, (b) is the ceramic fiber felt, (c) is the ceramic fiber felt treated at 1500°C for 20h, (d) is the ceramic fiber felt treated at 1500°C for 40h, and (e) is the ceramic fiber felt treated at 1500°C for 60h;
[0066] Fig.15 This is a SEM image of the SiC multi-scale nano / micro ceramic fiber felt matrix in Comparative Example 2;
[0067] Fig.16 This is a SEM image of the SiC multi-scale nano / micro ceramic fiber felt matrix in Comparative Example 3;
[0068] Fig.17 The SEM images of the high temperature resistant ceramic fiber felt precursor and the high temperature resistant ceramic fiber felt in Comparative Example 4, wherein (a) is the high temperature resistant ceramic fiber felt precursor, (b) is the high temperature resistant ceramic fiber felt magnified 200 times, and (c) is the high temperature resistant ceramic fiber felt magnified 1500 times;
[0069] Fig.18 The SEM images of the high temperature resistant ceramic fiber felt precursor and the high temperature resistant ceramic fiber felt in Comparative Example 5, wherein (a) is the high temperature resistant ceramic fiber felt precursor, (b) is the high temperature resistant ceramic fiber felt magnified 200 times, and (c) is the high temperature resistant ceramic fiber felt magnified 1500 times;
[0070] Fig.19 The SEM images of the high temperature resistant ceramic fiber felt prepared in Comparative Example 6 at different magnifications, wherein (a) is 200 times, (b) is 5000 times, (c) is 5000 times, and (d) is 10000 times;
[0071] Fig. 20 These are SEM images of the high temperature resistant ceramic fiber felt prepared in Comparative Example 7 at different magnifications, where (a) is 200 times, (b) is 5000 times, (c) is 5000 times, and (d) is 10000 times. DETAILED DESCRIPTION
[0072] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0073] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0074] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0075] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0076] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0077] The hydrochloric acid used in the specific implementation manner of the present invention is a commercially available product with a mass fraction of 36.8%.
[0078] The SiC nanowires used in the following embodiments of the present invention are prepared by carbon thermal reduction method using carbon fiber felt as a matrix, and the SiC micron fibers are provided by Fujian Jianya New Materials Co., Ltd.
[0079] The anionic surfactant used in the specific embodiment of the present invention is sodium dodecylbenzene sulfonate. The hydrophobic groups that are soluble in water and ionized with negative charge in the present invention are more inclined to combine with SiC nanowires, making the surface of the nanowires negatively charged. Therefore, based on the above content, when other anionic surfactants defined in the present invention are used, it does not affect the realization of the technical effects and can be replaced equally.
[0080] The cationic surfactant used in the specific embodiment of the present invention is hexadecyltrimethylammonium bromide. The water-soluble, ionized, positively charged hydrophobic groups in the present invention are more inclined to combine with SiC micron fibers, making the surface of the nanowires positively charged. Therefore, based on the above content, when other cationic surfactants defined in the present invention are used, it does not affect the realization of the technical effects and can be replaced equally.
[0081] The polar organic solvent used in the specific embodiment of the present invention is N,N-dimethylformamide (DMF), which plays a role in the present invention to reduce the surface tension of the solution and improve the compatibility between the fiber and the solvent. Therefore, based on the above content, when other organic polar solvents with similar surface tension defined in the present invention are selected, it does not affect the realization of the technical effect and can be replaced equally.
[0082] The organosilicon source used in the specific embodiment of the present invention is TEOS, MTES and TMES mixed in a molar ratio of 3:2:1. Its role in the present invention is to form a chemically stable silica sol protective agent. Therefore, based on the above content, when other organosilicon sources specified in this application are selected, it does not affect the realization of the technical effects and can be replaced equally.
[0083] The stabilizer used in the specific embodiment of the present invention is polyvinyl alcohol, and its role in the present invention is to increase the overall viscosity of the solution and ensure that the fibers can be suspended in the solution for a long time. Therefore, based on the above content, when other stabilizers with a certain viscosity specified in the present invention are selected, it does not affect the realization of the technical effect and can be replaced equally.
[0084] Example 1
[0085] The preparation steps of high temperature resistant ceramic fiber felt are as follows:
[0086] S1. Preparation of SiC nanowire dispersion:
[0087] Polyvinyl alcohol, anionic surfactant (sodium dodecylbenzene sulfonate) and water were mixed at a mass ratio of 1:3:1000, and after being fully dissolved, an active dispersion A was obtained. Then SiC nanowires were mixed with the active dispersion A at a mass ratio of 1:400, and ultrasonically dispersed for 30 minutes to obtain a SiC nanowire dispersion.
[0088] S2. Preparation of SiC micron fiber dispersion:
[0089] Polyvinyl alcohol, a cationic surfactant (hexadecyltrimethylammonium bromide), N,N-dimethylformamide (DMF) and water were mixed at a mass ratio of 1:3:100:1000, and after being fully dissolved, an active dispersion B was obtained. Short-cut SiC micron fibers were then mixed with the active dispersion B at a mass ratio of 1:1000, and ultrasonically dispersed for 30 minutes to obtain a SiC micron fiber dispersion.
[0090] Preparation of S3, SiC multi-scale nano / micro ceramic fiber felt matrix:
[0091] The SiC micron fiber dispersion and the SiC nanowire dispersion were successively poured into a suction filtration device, the mass ratio of the SiC micron fibers in the SiC micron fiber dispersion to the SiC nanowires in the SiC nanowire dispersion was 7:2, the fibers were first compacted in a static state, and then vacuum filtered, the pressure was maintained at 0.6-0.8 MPa, and the above process was repeated 24 times to obtain a SiC multi-scale nano / micro ceramic fiber felt matrix with a certain thickness (25 layers);
[0092] S4. Preparation of silica sol protective agent:
[0093] The organosilicon source (TEOS, MTES and TMES were mixed in a molar ratio of 3:2:1), ethanol and water were mixed in a molar ratio of 1:8:6, and hydrochloric acid was added dropwise at a stirring speed of 400 rpm for 30 min. The molar ratio of hydrochloric acid to organosilicon source was 1×10 -4 :1, after the addition is completed, stir under closed conditions for 12 to 20 hours to hydrolyze the organosilicon source to obtain an organosilicon sol;
[0094] Dispersing the organosilicon sol in anhydrous ethanol, the volume ratio of the organosilicon sol to the anhydrous ethanol is 1:29, to obtain a silica sol protective agent, at which the mass concentration of the organosilicon source in the silica sol protective agent is about 1.5%;
[0095] S5. The silica sol protective agent prepared in step S4 is filtered through the SiC multi-scale nano / micron ceramic fiber felt matrix prepared in step S3, the vacuum degree of the filtration is maintained at -0.1~0.08MPa, the volume / mass ratio of the silica sol protective agent and the SiC multi-scale nano / micron ceramic fiber felt matrix is 100mL:2.5g, and then washed with clean water several times, and dried in a temperature range of 120~150°C for 24h to obtain a high temperature resistant ceramic fiber felt precursor (SiC multi-scale ceramic fiber felt coated with silica sol protective agent);
[0096] S6. The high temperature resistant ceramic fiber felt precursor is heat treated at 1300°C for 1 hour and cooled to obtain SiO2-coated SiC multi-scale ceramic fiber felt, which is a high temperature resistant ceramic fiber felt, recorded as SiO2@SiC multi-scale fiber composite felt.
[0097] Figure 1 The SEM images of the SiC multi-scale nano / micro ceramic fiber felt matrix in Example 1 at different magnifications, where (a) is 30 times and (b) is 4000 times. Figure 1 It can be seen that the SiC nanowires are relatively evenly wrapped on the SiC micron fibers.
[0098] Figure 2 This is a physical picture of the high temperature resistant ceramic fiber felt prepared in Example 1. Figure 2 It can be seen that its diameter is about 50mm and its thickness is about 13mm.
[0099] Figure 3 The SEM images of the high temperature resistant ceramic fiber felt precursor and the high temperature resistant ceramic fiber felt, where (a) is the high temperature resistant ceramic fiber felt precursor, (b) is the high temperature resistant ceramic fiber felt magnified 200 times, and (c) is the high temperature resistant ceramic fiber felt magnified 1000 times. Figure 3 It can be seen that after heat treatment at 1300℃, silica sol exists on the surface of the micron fiber of the high temperature resistant ceramic fiber felt, and the SiC nanowires are wrapped with glass-like substances. At the same time, it is found that the silica sol protective agent tends to wrap the SiC nanowires more; the SiC nanowires are more evenly wrapped on the SiC micron fiber, which leads to the silica sol protective agent wrapping the SiC micron fiber evenly. At the same time, the SiC nanowires in the pores of the SiC micron fiber are also wrapped by the silica sol protective agent, which plays a connecting role between the SiC micron fibers. In this way, a dense and uniform glass coating is formed on the surface of the SiC micron fiber, which significantly improves the high temperature resistance of the high temperature resistant ceramic fiber felt.
[0100] The high temperature resistance of the high temperature resistant ceramic fiber felt prepared in Example 1 was investigated. The results are as follows: Figure 4 shown.
[0101] Figure 4 The SEM images of the high temperature resistant ceramic fiber felt prepared in Example 1 before and after high temperature treatment, where (a) is before high temperature treatment, (b) is after heat treatment at 1500℃ for 20h, (c) is after heat treatment at 1500℃ for 40h, and (d) is after heat treatment at 1500℃ for 60h. Figure 4 It can be seen that a layer of glass phase material wrapped on the surface of SiC micron fiber plays a role in protecting the fiber during high-temperature heat treatment and preventing the fiber from oxidative cracking.
[0102] The high temperature resistant ceramic fiber felt prepared in Example 1 was subjected to a cyclic heat treatment at 1500°C for 100 hours (20 hours as one interval, first heat treatment for 20 hours, then compression after cooling to room temperature, and resilience test, then heat treatment for 20 hours, then compression after cooling to room temperature, and resilience test, and this cycle) and the compression resilience test was as follows: Figure 5 shown.
[0103] Figure 5The compression rebound properties of the high temperature resistant ceramic fiber felt in Example 1 after being treated at 1500°C for different time periods, where (a) is 0h, (b) is 20h, (c) is 40h, (d) is 60h, (e) is 80h, and (f) is 100h. Figure 5 It can be seen that the ceramic fiber felt maintains good compression rebound performance after 1500℃, 100h cyclic heat treatment (20h as an interval, for example, first heat treat for 20h, cool to room temperature and then compress, test the rebound performance, then continue heat treat for 20h, cool to room temperature and then compress, test the rebound performance, and repeat this cycle), and the stress when compressed by 20% is stable at about 0.004MPa.
[0104] Figure 6 is the resilience of the high temperature resistant ceramic fiber felt in Example 1 after being compressed to 50% after 100h cyclic heat treatment at 1500°C, Figure 6 It can be seen that after 1500℃, 100h cyclic heat treatment, it can still maintain a certain rebound performance when compressed to 50%.
[0105] Example 2
[0106] Compared with Example 1, the only difference is that in step S3, the mass ratio of SiC micron fibers in the SiC micron fiber dispersion to SiC nanowires in the SiC nanowire dispersion is 7:4.
[0107] Figure 7 These are SEM images of the high temperature resistant ceramic fiber felt in Example 2 at different magnifications after being treated at 1500°C for 60 hours, where (a) is 100 times, (b) is 500 times, and (c) is 1000 times.
[0108] Example 3
[0109] Compared with Example 1, the only difference is that in step S3, the mass ratio of SiC micron fibers in the SiC micron fiber dispersion to SiC nanowires in the SiC nanowire dispersion is 7:5.
[0110] Figure 8 These are SEM images of the high temperature resistant ceramic fiber felt in Example 3 at different magnifications after being treated at 1500°C for 60 hours, where (a) is 37 times, (b) is 300 times, and (c) is 1000 times.
[0111] Example 4
[0112] Compared with Example 1, the only difference is that in step S3, the mass ratio of SiC micron fibers in the SiC micron fiber dispersion to SiC nanowires in the SiC nanowire dispersion is 7:3.
[0113] Fig. 9 These are SEM images of the high temperature resistant ceramic fiber felt in Example 4 at different magnifications after being treated at 1500°C for 60 hours, where (a) is 100 times, (b) is 1000 times, and (c) is 850 times.
[0114] Comparing the SEM images of Examples 1 to 4, it can be seen that with the increase of SiC nanowire content, SiC nanowires tend to agglomerate along the surface of SiC micron fibers, while the silica sol protective agent tends to adhere to the area where SiC nanowires are relatively concentrated. Figures 7-9 It can be seen that the uneven distribution of SiC nanowires leads to a small amount of oxidation cracking on the surface of SiC microfibers not wrapped by the protective agent in a high-temperature oxygen environment.
[0115] Example 5
[0116] Compared with Example 1, the only difference is that in step S3, the mass ratio of SiC micron fibers in the SiC micron fiber dispersion to SiC nanowires in the SiC nanowire dispersion is 7:1.
[0117] Fig.10 The SEM images of the high temperature resistant ceramic fiber felt in Example 5 after being treated at 1500°C for 60 hours at different magnifications are shown in Figure 5, where (a) is 35 times, (b) is 1000 times, and (c) is 1000 times. Compared with the heat resistance of Comparative Example 1, Fig.10 It can be seen that although the SiC nanowire content is too low, resulting in some oxidation cracking of some SiC micron fibers due to long-term exposure to high-temperature aerobic conditions, it still has excellent temperature resistance compared with the solution without adding SiC nanowires in the control example.
[0118] Example 6
[0119] Compared with Example 1, the only difference is that in step S3, the mass ratio of SiC micron fibers in the SiC micron fiber dispersion to SiC nanowires in the SiC nanowire dispersion is 1:1.
[0120] Fig.11 The SEM images of the high temperature resistant ceramic fiber felt in Example 6 after being treated at 1500°C for 60 hours at different magnifications, where (a) is 35 times, (b) is 950 times, and (c) is 1000 times. Fig.11 It can be seen that compared with Examples 1 to 5, the excess SiC nanowires are not wrapped on the surface of the SiC microfibers, but are distributed in the pores of the overlapped SiC microfibers, making the silica sol protective agent more inclined to wrap the SiC nanowires, and the SiC microfibers are oxidized and cracked when exposed to a high temperature oxygen environment for a long time.
[0121] Example 7
[0122] Compared with Example 1, the only difference is that in step S1, polyvinyl alcohol, anionic surfactant (sodium dodecylbenzene sulfonate) and water are mixed in a mass ratio of 1:1:1000.
[0123] Example 8
[0124] Compared with Example 1, the only difference is that in step S1, polyvinyl alcohol is mixed with a cationic surfactant (hexadecyltrimethylammonium bromide), N,N-dimethylformamide (DMF) and water in a mass ratio of 1:1:100:1000.
[0125] Fig.12 The SEM images of the high temperature resistant ceramic fiber felt precursors in Examples 7 and 8, wherein (a) to (b) are from Example 7, (c) to (d) are from Example 8, and Fig.12 It can be seen that compared with Example 1, the reduction in the content of the cationic surfactant or the anionic surfactant in Examples 7 to 8 leads to the agglomeration of the SiC microfibers or the SiC nanowires, and the content of the SiC nanowires on the surface of the SiC microfibers is low, but the SiC nanowires are relatively evenly distributed on the surface of the SiC microfibers, so the compression rebound performance is not much different from that in Example 1 (Table 1).
[0126] Example 9
[0127] Compared with Example 1, the only difference is that in step S1, polyvinyl alcohol, anionic surfactant (sodium dodecylbenzene sulfonate) and water are mixed in a mass ratio of 1:5:1000.
[0128] Example 10
[0129] Compared with Example 1, the only difference is that in step S2, polyvinyl alcohol, a cationic surfactant (hexadecyltrimethylammonium bromide), N,N-dimethylformamide (DMF) and water are mixed in a mass ratio of 1:5:100:1000.
[0130] Fig.13 The SEM images of the high temperature resistant ceramic fiber felt precursors in Examples 9 and 10, wherein (a) is Example 9, and (b) is Example 10. Fig.13 It can be seen that compared with Example 1, the content of cationic surfactant or anionic surfactant in Examples 9 to 10 is too high, which will lead to the neutralization of the charge of the charged ions in the solution and the charge of the SiC microfibers or SiC nanowires. During the filter pressing process, the SiC nanowires will agglomerate on the surface of the microfibers, but the compression rebound performance is not much different from that in Example 1 (Table 1).
[0131] Comparative Example 1
[0132] The preparation steps of ceramic fiber felt are as follows:
[0133] S1. Preparation of SiC micron fiber dispersion:
[0134] Polyvinyl alcohol, a cationic surfactant (hexadecyltrimethylammonium bromide), N,N-dimethylformamide (DMF) and water were mixed at a mass ratio of 1:5:100:1000, and after being fully dissolved, an active dispersion was obtained, and short-cut SiC micron fibers were mixed with the active dispersion at a mass ratio of 1:1000, and ultrasonically dispersed for 30 minutes to obtain a SiC micron fiber dispersion;
[0135] S2. Preparation of SiC ceramic fiber felt matrix:
[0136] Pour the SiC micron fiber dispersion into a suction filtration device, compact the fibers in a static state, and then perform vacuum filtration with the pressure maintained at 0.6-0.8 MPa. Repeat the above process 24 times to obtain a 25-layer SiC ceramic fiber felt matrix.
[0137] S3. Preparation of silica sol protective agent:
[0138] The organosilicon source (TEOS, MTES and TMES were mixed in a molar ratio of 3:2:1), ethanol and water were mixed in a molar ratio of 1:8:6, and hydrochloric acid was added dropwise at a stirring speed of 400 rpm for 30 min. The molar ratio of hydrochloric acid to organosilicon source was 1×10 -4 :1, after the addition is completed, stir under closed conditions for 12 to 20 hours to hydrolyze the organosilicon source to obtain an organosilicon sol;
[0139] Dispersing the organosilicon sol in anhydrous ethanol, the volume ratio of the organosilicon sol to the anhydrous ethanol is 1:29, to obtain a silica sol protective agent, at which the mass concentration of the organosilicon source in the silica sol protective agent is 1.5%;
[0140] S4, filtering the silica sol protective agent prepared in step S3 through the SiC ceramic fiber felt matrix prepared in step S2, the filtration pressure is maintained at 0.6-0.8 MPa, the volume / mass ratio of the silica sol protective agent and the SiC ceramic fiber felt matrix is 100 mL:2.5 g, and then washing with clean water several times, and drying at 120-150° C. for 24 hours to obtain a ceramic fiber felt precursor;
[0141] S6. Heat-treating the ceramic fiber felt precursor at 1300° C. for 1 hour, and cooling to obtain a ceramic fiber felt.
[0142] The high temperature resistance of the ceramic fiber felt prepared in Comparative Example 1 was investigated. Fig.14 shown.
[0143] Fig.14The SEM images of the ceramic fiber felt precursor and the ceramic fiber felt before and after high temperature treatment prepared in Comparative Example 1, wherein (a) is the ceramic fiber felt precursor, (b) is the ceramic fiber felt, (c) is the ceramic fiber felt treated at 1500℃ for 20h, (d) is the ceramic fiber felt treated at 1500℃ for 40h, and (e) is the ceramic fiber felt treated at 1500℃ for 60h. The magnifications from left to right in (a) to (d) are 100 times, 1000 times, and 1000 times, respectively. Fig.14 It can be seen that, as shown in (a), the silica sol protective agent in the ceramic fiber felt precursor cannot completely wrap the micron fiber after drying, and exists in the form of particles on the fiber surface; as shown in (b), the ceramic fiber felt obtained after the ceramic fiber felt precursor is heat treated at 1300℃ for 1h, in which the silica sol protective agent changes from the original irregular shape to spherical particles; as shown in (c), after the ceramic fiber felt is treated at 1500℃ for 20h, cracks appear on the fiber surface, and some fibers show overall adhesion. This is caused by the flow of SiO2 amorphous phase along the fiber surface when the fiber surface is oxidized. As shown in (d) to (e), as the heat treatment time increases, the overall adhesion phenomenon tends to be a node connection at the fiber overlap, indicating that the oxidation structure is constantly melting and shrinking at a high temperature of 1500°C. When the heat treatment time reaches 60h, the SiC micron fiber breaks significantly, indicating that in the process of the oxidation connection between the fibers transforming from an overall connection to a node connection, the fiber felt also slowly transforms from an overall rigid structure to a local rigid structure. When a certain change node is reached, the local rigid structure at the fiber connection and the microcracks on the fiber surface jointly cause it to break when it is deformed.
[0144] Comparative Example 2
[0145] Compared with Example 1, the only difference is that the anionic surfactant (sodium dodecylbenzenesulfonate) in step S1 is replaced with an equal amount of cationic surfactant (hexadecyltrimethylammonium bromide).
[0146] Fig.15 This is a SEM image of the SiC multi-scale nano / micro ceramic fiber felt matrix in Comparative Example 2. Fig.15 It can be seen that since the same cationic surfactant is used for SiC nanowires and microfibers, compared with the coating effect of Example 1, it is found that the coating amount of SiC nanowires is much lower than that of Example 1, and the SiC nanowires are unevenly distributed on the SiC microfibers. Fig.14 From the heat resistance evaluation, it can be seen that the uneven distribution of SiC nanowires on the SiC micron fibers in Comparative Example 2 will lead to uneven distribution of the silica sol protective agent on the SiC micron fibers under high temperature environment, which will further affect the final heat resistance performance.
[0147] Comparative Example 3
[0148] Compared with Example 1, the only difference is that the cationic surfactant (hexadecyltrimethylammonium bromide) in step S2 is replaced by an equal amount of anionic surfactant (sodium dodecylbenzene sulfonate).
[0149] Fig.16 This is a SEM image of the SiC multi-scale nano / micro ceramic fiber felt matrix in Comparative Example 3. Fig.16 It can be seen that since the same anionic surfactant is used for SiC nanowires and microfibers, although the coating amount is higher than that of Comparative Example 2, compared with the coating effect of Example 1, it is found that the coating amount of SiC nanowires is still lower than that of Example 1, and the SiC nanowires are unevenly distributed on the SiC microfibers, thereby Fig.14 From the heat resistance evaluation, it can be seen that the uneven distribution of SiC nanowires on the SiC micron fibers in Comparative Example 3 will lead to uneven distribution of the silica sol protective agent on the SiC micron fibers under high temperature environment, which will further affect the final heat resistance performance.
[0150] Comparative Example 4
[0151] Compared with Example 1, the only difference is that the mass concentration of the organic silicon source in the silica sol protective agent in step S3 is 4%.
[0152] Fig.17 The SEM images of the high temperature resistant ceramic fiber felt precursor and the high temperature resistant ceramic fiber felt in Comparative Example 4, wherein (a) is the high temperature resistant ceramic fiber felt precursor, (b) is the high temperature resistant ceramic fiber felt magnified 200 times, and (c) is the high temperature resistant ceramic fiber felt magnified 1500 times. Fig.17 It can be seen that SiC micron fibers will be oriented and bonded together under the action of the fiber at high temperature.
[0153] Comparative Example 5
[0154] Compared with Example 1, the only difference is that the mass concentration of the organic silicon source in the silica sol protective agent in step S3 is 0.6%.
[0155] Fig.18 The SEM images of the high temperature resistant ceramic fiber felt precursor and the high temperature resistant ceramic fiber felt in Comparative Example 5, wherein (a) is the high temperature resistant ceramic fiber felt precursor, (b) is the high temperature resistant ceramic fiber felt magnified 200 times, and (c) is the high temperature resistant ceramic fiber felt magnified 1500 times. Fig.18 It can be seen that the silica sol protective agent cannot wrap the nanowires after high-temperature melting, resulting in the destruction of the fiber structure after heat treatment at 1300°C.
[0156] Comparative Example 6
[0157] Compared with Example 1, the only difference is that the heat treatment temperature in step S6 is 1100°C.
[0158] After heat treatment at 1100℃, the silica sol protective agent is wrapped in SiC micron fiber:
[0159] Fig.19 The SEM images of the high temperature resistant ceramic fiber felt prepared in Comparative Example 6 at different magnifications, where (a) is 200 times, (b) is 5000 times, (c) is 5000 times, and (d) is 10000 times. Fig.19 It can be seen that since no surfactant was added to disperse the SiC nanowires, the SiC nanowires were not wrapped on the surface of the SiC microfibers. After heat treatment, the silica sol protective agent was not transformed into a glass phase and had no time to wrap the SiC microfibers.
[0160] Comparative Example 7
[0161] Compared with Example 1, the only difference is that the heat treatment temperature in step S6 is 1500°C.
[0162] After heat treatment at 1500℃, the silica sol protective agent is wrapped in SiC micron fiber:
[0163] Fig. 20 The SEM images of the high temperature resistant ceramic fiber felt prepared in Comparative Example 7 at different magnifications, where (a) is 200 times, (b) is 5000 times, (c) is 5000 times, and (d) is 10000 times. Fig. 20 It can be seen that at a high temperature of 1500°C, the smooth surface of the SiC micron fiber intensifies the melt flow of the silica sol protective agent, and the surface of the SiC micron fiber is exposed to the air and oxidized to produce obvious microcracks.
[0164] In Comparative Examples 6 and 7, after heat treatment at 1100°C, the silica sol protective agent did not transform into a glass phase. At 1500°C, the melting flow of the silica sol protective agent intensified, and the surface of the SiC micron fiber was exposed to the air and oxidized to form obvious microcracks. However, when heat treated at 1200-1400°C, the silica sol protective agent could evenly coat the SiC micron wires and nanowires. In Comparative Example 1, there were no SiC nanowires bound on the surface of the SiC micron fiber, and the glass phase gradually agglomerated and shrunk, eventually leading to oxidation and cracking of the SiC fiber when exposed to the air.
[0165] Test example
[0166] The high temperature resistant ceramic fiber felts prepared in Examples 1 to 10 and Comparative Examples 1 to 7 were treated at 1500° C. for 60 hours and then compressed 10 times to measure their compression resilience (%). The results are shown in Table 1.
[0167] Table 1
[0168]
[0169] It can be seen from the data in Table 1 that the high temperature resistant ceramic fiber felt prepared in Examples 1 to 6 of the present invention still has excellent compression rebound rate after being treated at 1500°C for 60 hours and compressed 10 times. However, in Comparative Example 1, a single SiC micron fiber is used. Due to the lack of the directional effect of SiC nanowires, the silica sol protective agent cannot be evenly distributed on the surface of the SiC micron fiber. At the same time, the silica sol protective agent quickly melts and shrinks in a high temperature environment, and the internal stress of the material is concentrated, resulting in a significant decrease in the compression rebound rate. In Comparative Examples 2 to 3, the same surfactant is used when dispersing SiC nanowires and SiC microwires. Since the SiC nanowire coating amount on the surface of the SiC micron fiber is reduced, the coating effect of the silica sol protective agent on the micron fiber is affected, so that the compression rebound rate is lower than that of Example 5. The influence of the SiC nanowire coating amount on the compression rebound performance of the material is consistent with the change trend of Examples 1 to 6. In Comparative Examples 4 to 5, the mass concentration of the organic silicon source is too high or too low. When the silicon source concentration is too high, the micron fibers are oriented under the action of a large amount of silica sol protective agent, and the flexible structure of multi-scale micro-nano fibers is transformed into a rigid structure, and does not have compression resilience; when the silicon source concentration is too low, the silica sol protective agent cannot simultaneously wrap the SiC micron fibers and SiC nanowires, so that their compression resilience performance is reduced when exposed to a high-temperature oxygen environment for a long time compared with Examples 1 to 6. In Comparative Examples 6 to 7, the heat treatment temperature that is too high or too low affects the distribution state of the silica sol protective agent on the surface of the SiC micron fibers. Too high a temperature will cause the fibers to oxidize and crack prematurely, and too low a temperature will cause the silica sol protective agent to be unable to form a glass phase to wrap the fibers.
[0170] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a high temperature resistant ceramic fiber felt, characterized in that the steps include: dispersing SiC nanowires by using anionic surfactant to obtain SiC nanowire dispersion; The SiC micron fiber is dispersed by using a cationic surfactant to obtain a SiC micron fiber dispersion; The SiC nanowire dispersion and the SiC micron fiber dispersion are mixed and then subjected to filter pressing treatment, and the mixing-filter pressing treatment is repeated at least once to obtain a SiC multi-scale nano / micro ceramic fiber felt matrix; Passing the silica sol protective agent through the SiC multi-scale nano / micro ceramic fiber felt matrix by suction filtration, and washing and drying to obtain a high temperature resistant ceramic fiber felt precursor; The high temperature resistant ceramic fiber felt precursor is heat treated and then cooled to obtain the high temperature resistant ceramic fiber felt.
2. The preparation method according to claim 1, characterized in that: The step of dispersing SiC nanowires using anionic surfactants is as follows: After dissolving the stabilizer and the anionic surfactant in water, adding SiC nanowires and performing ultrasonic dispersion to obtain a SiC nanowire dispersion; The mass ratio of the stabilizer, the anionic surfactant and water is 1-3:1-5:1000-2000; the mass ratio of the sum of the mass of the stabilizer, the anionic surfactant and water to the mass of the SiC nanowire is 400-800:1; the ultrasonic dispersion time is 10-30 minutes; the anionic surfactant is at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, calcium stearate, sodium fatty alcohol sulfate and sodium ethoxylated fatty acid methyl ester sulfonate; the stabilizer includes at least one of polyethylene glycol, polyvinyl alcohol, carboxymethyl cellulose, hydroxymethyl cellulose and sodium alginate.
3. The preparation method according to claim 1, characterized in that: The step of dispersing SiC micron fibers using a cationic surfactant is as follows: After dissolving a stabilizer, a cationic surfactant and an organic polar solvent in water, SiC micron fibers are added and dispersed by ultrasonication to obtain a SiC micron fiber dispersion; The SiC micron fiber is a short-cut SiC micron fiber; the cationic surfactant is at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium bromide chloride, cetylpyridinium chloride, benzalkonium chloride and benzalkonium bromide; the organic polar solvent includes one of ethanol, propylene glycol, N,N-dimethylformamide, dimethylacetamide and N-methylpyrrolidone; the mass ratio of the stabilizer, the cationic surfactant, the organic polar solvent and water is 1-3:1-5:100-200:1000-2000; the mass ratio of the sum of the mass of the stabilizer, the cationic surfactant, the organic polar solvent and water to the mass of the SiC micron fiber is 500-1000:1; the ultrasonic dispersion time is 10-30 minutes; the stabilizer includes at least one of polyethylene glycol, polyvinyl alcohol, carboxymethyl cellulose, hydroxymethyl cellulose and sodium alginate.
4. The preparation method according to claim 1, characterized in that: The preparation steps of the silica sol protective agent are: The organosilicon source, ethanol and water are mixed in a molar ratio of 1:8-15:4-10, stirred at a speed of 300-500 rpm for 10-30 minutes, and then hydrochloric acid is added dropwise. After the addition is completed, the mixture is stirred for 12-20 hours under a closed condition to obtain an organosilicon sol; Then, the organic silica sol is dispersed in ethanol to obtain a silica sol protective agent; The organic silicon source comprises at least one of ethyl orthosilicate, methyltriethoxysilane and trimethylethoxysilane; the molar ratio of hydrochloric acid to the organic silicon source is 10 -4 ~10 -3 :1; The mass fraction of the organic silicon source in the silica sol protective agent is 1~3%.
5. The preparation method according to claim 1, characterized in that: The mass ratio of SiC micron fibers to SiC nanowires in the SiC multi-scale nano / micron ceramic fiber felt matrix is 1-7:1-10; and the pressure of the filter press is 0.6-0.8 MPa.
6. The preparation method according to claim 1, characterized in that: The vacuum degree of the filtration is -0.1~0.08MPa; the volume / mass ratio of the silica sol protective agent and the SiC multi-scale nano / micro ceramic fiber felt matrix is 80~120mL:2~3g.
7. The preparation method according to claim 1, characterized in that: The drying temperature is 120-150° C. and the drying time is 12-24 hours.
8. The preparation method according to claim 1, characterized in that: The heat treatment temperature is 1200-1400° C. and the time is 1-3 hours.
9. A high temperature resistant ceramic fiber felt obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the high temperature resistant ceramic fiber felt as claimed in claim 9 in high temperature equipment.
Citation Information
Patent Citations
Oxide ceramic fiber board
CN103524140A
Preparation method of high-temperature-resistant reinforced and toughened Ox / Ox composite material
CN112479691A